2004
DOI: 10.1117/12.536444
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized coherence in fiber laser arrays

Abstract: Self-organized coherence between fiber lasers has been reported both via all-fiber 2x2 directional coupler trees and in spatially multi-core fibers. We have taken this a major step forward, coupling together a number of independent fiber lasers to obtain a spatially and spectrally coherent far field, with no active length, polarization, or amplitude control. The near field output comes from a spatial array rather than from a single fiber, making this approach scalable to extremely high power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The unfilled aperture designation brings together methods that coherently combine an array of multiple identical laser beams [9][10][11]. Configuration for which laser beams are spatially separated in the near field and are superimposed in the far field is a common feature of this beam combining technique.…”
Section: Unfilled Aperturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The unfilled aperture designation brings together methods that coherently combine an array of multiple identical laser beams [9][10][11]. Configuration for which laser beams are spatially separated in the near field and are superimposed in the far field is a common feature of this beam combining technique.…”
Section: Unfilled Aperturesmentioning
confidence: 99%
“…The fibered nature of the laser system makes evanescent coupling simple by drawing locally the N fibres closer like a fused star coupler that has been cleaved across the narrowest part. Lately, a tapered bundle of seven fibres was connected to seven Neodymium doped fibres (110 mW per laser) to experiment such evanescent wave coupling method [10]. There was no symmetry in the coupler that was made from a twisted bundle of fibres in random position.…”
Section: Unfilled Aperturesmentioning
confidence: 99%
“…Here, it should be noted that, even with the nonzero time duration, the output phase states are not totally irregular. Actually, because of phase locking of the array, only certain phase states (i.e., the phase-locked states) can be exported from the array (see (17)). It is found that an N-laser array can output 2 N −1 phase-locked states.…”
Section: -10mentioning
confidence: 99%
“…31 Later, it was utilized to build the fiber laser array. Prior to the interference array (where only one port is used for output and the burden capability of the unique output port limits the power scaling of the whole array), [17][18][19][20][21][22][23][24][25][26] the array of mutually-injected fiber lasers adopts multiple output ports. Then, each output port only needs to burden the power of one elementary laser, and the power scaling of the whole array may not be limited.…”
Section: Introductionmentioning
confidence: 99%
“…Coherent beam combining of many fiber lasers is an important and challenging research topic for power scaling of single-mode fiber laser as well as for developing highly-functional fiber laser [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Achieving a single output of both high-power and high-brightness from many moderate-power lasers as well as coherent control of beam deflection without mechanical movements are goals which will promise a great number of scientific and industrial applications.…”
Section: Introductionmentioning
confidence: 99%